Filming in the home: A reflexive account of microethnographic data collection with family caregivers of older adults - Silverman, Marjorie (Université d'Ottawa | University of Ottawa, 2016)
This article explores the impact of the researcher’s reflexivity on the data collection and analysis process in the context of a videographic study of home-based family caregivers of older adults. Going beyond a discussion of the role of the researcher’s subjectivity, the article builds on current literature by exploring how the researcher’s embodied self- reflexivity can be used to enrich video based research. The article addresses the researcher’s personal social location and shifting roles throughout the study and how these impacted on her work with the camera, her moment to moment ethical decisions and her perceptions of the participants’ realities. The author illustrates, through the use of journal and transcript excerpts, how the dynamic relationship between the researcher, the participants and the camera creates overlapping and complementary layers of information that together form a cohesive portrait of the action. Throughout, the article discusses the contribution of reflexivity to both the creation and resolution of ethical tensions in the research space.